Implementing Knowledge Management in the Palestinian Public Sector Institutions: Empirical Study on the Presidency of the Palestinian Government - Almudallal, Abdullah Waleed; Bakri, Norhani; Muktar, Syaharizatul Noorizwan; El-Farra, Majed M. (International Review of Management and Marketing, 2016)
This paper focuses on bridging the theoretical and empirical approaches of KM key enablers in the Palestinian public sector, which are essential to facilitate and ensure a successful implementation of KM; these key enablers are: Organizational Culture, Leadership, Personnel, Information technology. For this purpose, a questionnaire was personally distributed to all (46) technical, administrative, and supervisory employees working at the Presidency of the Palestinian Government. Total of (44) fully answered questionnaires were received. The results showed a significant positive relationship between KM key enablers and the level of performance in the Palestinian Ministers’ Council by 0.829. It also indicated that 70% of the variation in the performance level has been significantly explained and influenced by KM key enablers. The recommendations proposed by this paper will provide a strategic direction for the Palestinian public administration to act more effectively with KM practices, and pay a focused attention to its key enablers. Keywords: Knowledge Management; Public Sector; Palestine. JEL Classifications: D80; H11; M10